Elaboración de una bebida funcional hipocalórica con colágeno hidrolizado - Inca Murillo, Kerly Nathaly (2024)
At present, there are very few low-calorie functional beverages that meet the nutritional requirements in humans without providing considerable amounts of sugars, which poses a risk for people with hypertension and diabetes. This research focuses on elaboration a hypocaloric functional beverage with added hydrolyzed collagen, whose contribution of proteins, antioxidants, vitamins, and electrolytes allows it to be considered an alternative beverage to the traditional ones. Three different treatments were formulated with three replicates each, T1: 40% blueberry-grape juice (ZAU); 8% mint-balm infusion (IMT); 2,2% peppermint extract (EH); 0,3% Stevia (S); 48% water (A); 1,5% hydrolyzed collagen (CH); T2: 37% ZAU; 9% IMT; 2,2% EH; 0,3% S; 50%A; 1;5% CH; and T3: 34% ZAU: 10% IMT; 2,2% EH; 0,3% S; 5,2% A; 1,5% CH, respectively. The raw material was selected under the parameters of the NTE INEN 2 337:2008 Standard, and the grape blueberry juice was extracted with the help of a blender. Then, the mint-balm infusions were prepared by placing the leaves separately in boiling water and resting for 5 minutes; later, the mint extract was obtained with the help of a mortar. Finally, the ingredients were mixed in the established proportions and bottled in sterilized glass bottles. The evaluation of the quality of the beverage was based on compliance with the same standard, which establishes the determination of physicochemical and microbiological parameters. The results showed that T1 was the best treatment, determined by physicochemical, microbiological, sensory, and statistical analysis due to its freshness and higher percentage of juice. Treatment T1 presented a protein unit of 1,47% and for anthocyanin of 55,77 mg/250mL . In addition, a product data sheet was prepared, highlighting the nutritional characteristics and generating consumer confidence